PERSUASIVE COMMUNICATION USED BY INSURANCE AGENTS OF SELLING PROSPECT IN PRESTASI AGENCY BINJAI - Muhammad Iqbal Dary; Zuindra Zuindra; Hendra Mulia (Lembaga Pengembangan Kinerja Dosen, 2022)
The persuasive language used by agents is able to change the thoughts and feelings of the prospective customer until the opinion that conveyed by the agent is carried out reaches its main purpose, closing. The researcher sees a phenomenon among agents where they have offices in the same place, then have the same coach and training model, but in the end of the day the results seen from their sales figures vary from one another. This research aims to analyze what persuasive strategies are used in sales and the relationship between persuasive language and speech acts. The theories used in this research are pragmatics and communication. Speech acts in this research used as the support theory of the pragmatics. The researcher used qualitative research methods to analyze the data. The result, the researcher got 14 data in analysis of persuasive strategies and illocutionary act. There are, 6 data of enhancing credibility, 4 data of using logic and evidence to persuade and 4 data of using emotion to persuade. The researcher found the most frequently used strategy is Using logic and evidence and Enhancing credibility with competence. From the analysis the researcher also found there two sales methods, soft selling and hard selling.